Tracking Loss Recovery for Relative UWB Tag Positioning in AR-IoT Applications - Choi, Hong Beom; Lim, Keun Woo; Ko, Young Bae (Journal of Korean Institute of Communications and Information Sciences, 2020)
In this paper, we assume a tag relative positioning system that combines vSLAM technology and indoor positioning technology using UWB in augmented reality application environment. In this case, we presented three methods to recover the tracking loss that can occur in vSLAM using the tag relative positioning system, and implemented and tested them.
Keywords: Augmented Reality; Indoor Positioning; Internet of Things; Relative Positioning; UWB; vSLAM